Recent Advances on Drug Development and Emerging Therapeutic Agents Through Targeting Cellular Homeostasis for Ageing and Cardiovascular Disease - Azam, Tayyiba; Zhang, Hongyuan; Zhou, Fangchao; Wang, Xin (Frontiers in Aging, 2022)
Ageing is a progressive physiological process mediated by changes in biological pathways, resulting in a decline in tissue and cellular function. It is a driving factor in numerous age-related diseases including cardiovascular diseases (CVDs). Cardiomyopathies, hypertension, ischaemic heart disease, and heart failure are some of the age-related CVDs that are the leading causes of death worldwide. Although individual CVDs have distinct clinical and pathophysiological manifestations, a disturbance in cellular homeostasis underlies the majority of diseases which is further compounded with aging. Three key evolutionary conserved signalling pathways, namely, autophagy, mitophagy and the unfolded protein response (UPR) are involved in eliminating damaged and dysfunctional organelle, misfolded proteins, lipids and nucleic acids, together these molecular processes protect and preserve cellular homeostasis. However, amongst the numerous molecular changes during ageing, a decline in the signalling of these key molecular processes occurs. This decline also increases the susceptibility of damage following a stressful insult, promoting the development and pathogenesis of CVDs. In this review, we discuss the role of autophagy, mitophagy and UPR signalling with respect to ageing and cardiac disease. We also highlight potential therapeutic strategies aimed at restoring/rebalancing autophagy and UPR signalling to maintain cellular homeostasis, thus mitigating the pathological effects of ageing and CVDs. Finally, we highlight some limitations that are likely hindering scientific drug research in this field.